2004
DOI: 10.1097/01.mej.0000129168.43816.c1
|View full text |Cite
|
Sign up to set email alerts
|

Microscooter injuries in the paediatric population

Abstract: The popularity of microscooters seems to represent a significant risk of bony injury in the paediatric population. Medical personnel who manage acute paediatric trauma should be aware of scooter-related triplanar ankle injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Children are at risk for physeal ankle injury in sports requiring sudden changes in direction, such as basketball, soccer, and football 4 . Scooters and skateboards are also associated with a high risk of ankle injuries 5,6 .…”
Section: Epidemiologymentioning
confidence: 99%
“…Children are at risk for physeal ankle injury in sports requiring sudden changes in direction, such as basketball, soccer, and football 4 . Scooters and skateboards are also associated with a high risk of ankle injuries 5,6 .…”
Section: Epidemiologymentioning
confidence: 99%
“…6, 7 Basketball, soccer, football, and scooters are the most common activities associated with ankle fractures. 81011 …”
Section: Epidemiologymentioning
confidence: 99%
“…These injuries are commonly mild and self-resolving, [1][2][3] but a small proportion can result in significant morbidity and mortality. About 2 to 20% of scooter-related injuries seen in emergency departments (EDs) require hospitalisation, 2,4,5 surgery, 4,6 intensive care unit (ICU) stay or result in death. 2,7,8 There is an increasing trend of injuries related to AMD use.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Keays et al 9 found a higher proportion of head and neck injuries in longboarders when compared to lower limb extremities in skateboarders, while Aslam et el. 6 highlighted the risk of triplanar ankle fractures from scooter use. Injury prevalence and type…”
Section: Introductionmentioning
confidence: 99%